Tatakelola Keuangan Rumah Tangga Islami Menggunakan Aplikasi Money Lover Sebagai Upaya Peningkataan Manajemen Resiko Keuangan Keluarga - Salam Salam; Syarthini Indrayani; Abdul Khaliq; Mira Mira (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service aims to increase literacy and Islamic financial management by using the money lover app for housewives in the village of Galesong Baru, Takalar Regency. The method used in this Service was Community Development Practice with three requirements that must be met: community-based, local resource-based, and sustainable. At the same time, the training process began with 1) Conducting outreach to educate financial literacy housewives, 2) Preparing a routine/non-routine income and expenditure budget plan, 3) Making a list of income and expenses in the Money Lover App, 4) At the evaluation stage it was carried out by looking at the ability of PKK mothers to fill in the Money Lover App application divided with the total number of PKK mothers involved in the activity. The results of this community service activity showed thatÂ PKK Kec. Galesong already knew financial literacy and could use the Money Lover app to record the amount of household income and expenditures earned. So, if there are non-value-added expenditures (which are consumptive), they can be reduced and maximize existing finances to meet primary and secondary needs. It can plan savings for the future.